Exploring the Effectiveness of a Virtual Coaching Program to Support Staff Working at Families as First Teachers Playgroups in the Remote Northern Territory, Australia - Jane Page; Isabel Brookes; Catriona Elek; Patricia Eadie; Lisa Murray (Education Sciences)
Coaching is an important form of professional development for the early childhood education and care (ECEC) workforce. However, educators working in remote contexts do not always have access to this type of support. This paper explores the effectiveness of a virtual (online and telephone) coaching program focusing on the implementation of evidence-informed Conversational Reading strategies in supported playgroups for Aboriginal families in the Northern Territory of Australia. Fourteen Family Educators and Family Liaison Officers across ten Families as First Teachers playgroups in the Northern Territory participated in the coaching program over twelve months. Coaching records, planning documents, participant feedback, and video recordings of participants’ practice were analysed to explore the impact and acceptability of the coaching program. The findings indicate that participation in the cycle of virtual coaching, planning, and reflection supported participants in implementing evidence-informed teaching strategies, offering language-rich experiences to children frequently and with increased fidelity, and engaging with families about their use of these strategies in the home. The model of coaching developed shows promise for wider implementation in ECEC contexts, particularly in remote communities where access to high-quality professional learning and development can be limited.